Uso de saponina de quilaia (Quillaja saponaria Molina) em juvenis de pacu - Fernandes, Rosangela do Nascimento [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The quillaja saponin (QS) is present in the bark of Chilean and Brazilian trees of the same family, Rosaceae and, it´s able to promote performance and the immune system of animals. Thus, this study evaluated the effect of consuming diets containing increasing levels of QS (0,0; 100,0; 200,0; 300,0; 400,0 mg kg-1) by pacu. Three distinct steps in different consumption diets periods compound by seven, 15, and 30 days. At each step, was used a total of 350 fish, totaling 1050 fishes. These fishes were distributed into 25 cages (200L), in a completely randomized design. In the second chapter, after the feeding period (seven, 15 and 30 days), fish were anesthetized to blood collect and organs for physiological, histological and performance evaluation. The parameters evaluated were the performance (weight gain, apparent feed conversion and feed intake), survival, physiological and histological parameters [hepatosomatic index (HSI), blood cortisol, glucose, cholesterol, triglycerides and intestine histology]. The addition of all levels of QS in the diets of juvenile pacu reduced the triglycerides levels at seven days and HSI at 30 days of feeding. At 15 days of feeding QS diets were observed signals intestinal inflammation in pacu. There was no mortality during the experimental period. In the third chapter, after the feeding period (seven, 15 and 30 days), about 325 fishes were inoculated with the Aeromonas hydrophila and transferred to another experimental system, divided into 25 cages (160L) and during six days were observed clinical signs of disease and occurrence of mortality. The fishes were anesthetized for blood collection before and after bacterial challenge. The physiological analyzes were glucose, total protein and albumin. The immunological variables measured were activity serum lysozyme, leukocytes respiratory activity (LRA), differential and leukocyte count and globulin and ...

A saponina de quilaia (SQ) está presente na casca de árvores chilenas e brasileiras da mesma família, Rosaceae e, de acordo com relatos, melhora o desempenho zootécnico e atua no sistema imune de aves, ratos, camarões e peixes. Assim sendo, este estudo objetivou avaliar os efeitos da inclusão de níveis crescentes de extrato purificado de SQ (0,0; 100,0; 200,0; 300,0; 400,0 mg kg-1) para juvenis de pacu. O estudo teve três etapas experimentais distintas, compostas por períodos de consumo da dieta por sete, 15 e 30 dias. Em cada etapa, foram utilizados 350 peixes, totalizando 1050 peixes. Esses foram distribuídos em 25 aquários (200L), num delineamento inteiramente casualizado. No segundo capítulo, os peixes foram anestesiados para a coleta de sangue e órgãos (fígado e intestino). Os parâmetros avaliados foram desempenho (ganho de peso, conversão alimentar e consumo de ração), sobrevivência, parâmetros fisiológicos e histológicos [glicose, cortisol, proteína total, colesterol, triglicerídeos, índice hepatossomático (IHS) e histologia de intestino]. Houve alteração no perfil de lipídios circulantes, com redução do IHS aos 30 dias e das concentrações séricas de triglicerídeos aos sete dias de consumo de SQ, respectivamente. Com 15 dias, foram observados sinais de inflamação no intestino do pacu. Não houve mortalidade durante o período de alimentação dos peixes. No terceiro capítulo, após o período de alimentação, cerca de 325 peixes foram inoculados com a bactéria Aeromonas hydrophila e transferidos para outro sistema experimental, sendo distribuídos em 25 aquários (160L), onde foram observados durante seis dias, quanto aos sinais clínicos da doença e ocorrência de mortalidade. Os peixes foram anestesiados para a coleta de sangue antes e após o desafio bacteriano. As análises fisiológicas foram de glicose, proteína total, albumina e globulina ...
Keywords: Peixe - Nutrição; Pacu (Peixe); Imunidade celular; Triglicérides; Sistema imune; Fishes